2018
DOI: 10.1089/humc.2017.249
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Double-Blind, Phase III Clinical Trial to Evaluate the Efficacy and Safety of a Cell and Gene Therapy in Knee Osteoarthritis Patients

Abstract: The aim of this study was to test the clinical efficacy of TissueGene-C (TG-C), a cell and gene therapeutic for osteoarthritis consisting of non-transformed and transduced chondrocytes (3:1) retrovirally transduced to overexpress transforming growth factor-β1. A total of 163 Kellgren-Lawrence grade 3 patients with knee osteoarthritis were randomly assigned to receive intra-articular TG-C or placebo. Primary efficacy measures included criteria for subjective assessment by International Knee Documentation Commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…In this study, 163 patients with Kellgren-Lawrence grade III OA were randomly assigned to receive a single intra-articular injection of TissueGene C or saline. The study met both of its primary outcomes of showing statistically significant improvements in IKDC (+15 versus +5; P < 0.001) and VAS (−25 points versus −10 points; P < 0.001) scores at 52 weeks compared with control 184 . The IKDC and VAS scores were also improved at week-26 and week-39, and statistically significant improvements were seen in secondary clinical outcomes (WOMAC and KOOS) at week-52 compared with control.…”
Section: The Intra-articular Therapy Pipelinementioning
confidence: 87%
See 1 more Smart Citation
“…In this study, 163 patients with Kellgren-Lawrence grade III OA were randomly assigned to receive a single intra-articular injection of TissueGene C or saline. The study met both of its primary outcomes of showing statistically significant improvements in IKDC (+15 versus +5; P < 0.001) and VAS (−25 points versus −10 points; P < 0.001) scores at 52 weeks compared with control 184 . The IKDC and VAS scores were also improved at week-26 and week-39, and statistically significant improvements were seen in secondary clinical outcomes (WOMAC and KOOS) at week-52 compared with control.…”
Section: The Intra-articular Therapy Pipelinementioning
confidence: 87%
“…Data from a multi-centre, double-blind, clinical trial conducted in South Korea revealed that TissueGene C provided long-term clinical benefits compared with placebo 184 . In this study, 163 patients with Kellgren-Lawrence grade III OA were randomly assigned to receive a single intra-articular injection of TissueGene C or saline.…”
Section: The Intra-articular Therapy Pipelinementioning
confidence: 99%
“…administration of fibroblast growth factor-18 (FGF18) has demonstrated chondroprotective effects in a bovine in vitro model[3], in an in vivo rat model[4] and in a randomized, double-blind, placebo-controlled trial, although pain relief was not achieved[5, 6]. Transforming growth factor-beta1 (TGF-β1) producing human chondrocytes were able to generate cartilage with hyaline-like characteristics in two different animal models[7] and demonstrated clinical benefits in multiple clinical trials[812] with small, not statistically significant but encouraging chondroprotective activity[8, 12, 13], and anti-inflammatory activity[13]. SM04690, a Wnt pathway inhibitor, induced chondrocyte differentiation, reduced cartilage catabolism in vitro , and showed chondroprotective activity in a rat model of OA[14], and in humans[15].…”
Section: Introductionmentioning
confidence: 99%
“…TGFB1 plays a critical role in skeletal development and adult bone homeostasis18, including bone remodelling19, osteoclast/osteoblast differentiation20,21 and chondrogenesis22. INVOSSA™, a TGFB1 cell and gene therapy in chondrocytes, was associated with significant improvements in function and pain in patients with knee osteoarthritis23.…”
mentioning
confidence: 99%